Arabic Language Curriculum as a Foundation for Strengthening Religious Education in Public Higher Education - Abd Aziz Rekan; Hafeezur Rahman Howell; Muhamad Nasir Mohamad Salleh; Nurhasfirah Rosin; Tabrani ZA; Muhammad Anas Ma`arif; Mohamad Azrien Mohamed Adnan (Jurnal Pendidikan Agama Islam)
Purpose – This study was conducted to examine the implementation of the Arabic Language Program (ALP) and to explore how Arabic functions as a foundational medium for the acquisition of Islamic knowledge at a public higher education institution in Malaysia.